Predictive Models of Front Crawl Swimming Achievement in Terms of Some Anthropometric, Physical and Kinematics Variables among Physical Education Students - Abu Altaieb, Mohammad Hassan; Aldababseh, Mohammad; Alawamleh, Zeikra Saad; Saada, Bilal Yousef (Dirasat: Educational Sciences, 2021)
This study aims to determine predictive models in terms of some anthropometric physical & kinematics variables regarding the (50 m) front crawl swimming achievement among physical education students. The study sample consisted (of 32) males who were assigned to swimming courses. The researcher used the descriptive method. The following anthropometric variables were measured: the trunk length, leg, foot, arm span, palm, total height, & body mass index (BMI). Physical variables values consisted of strength endurance to the chest muscles using Push-ups test, abdominal muscles using Sit-ups test, and 10RM of biceps, squat, and lat pull down. The kinematics variables consisted of (The time of (50m) front crawl swimming, arms stroke length, arms stroke rate, velocity of (50m) front crawl swimming, and the efficiency factor). To analyze the data statistically, means, standard deviations, Pearson correlation coefficient, and Stepwise Multiple Linear Regression. The results of the study indicated that it is possible to predict the time achievement of (50 m) front crawl swimming through the following variables that have the highest contribution: arms length, the strength endurance of chest, abdominal muscles, and swimming velocity). The researchers recommended developing the swimming skill performance for physical education students by attention to variables that can predict (50 m) front crawl swimming achievement as their contribution ratios.